Hubungan Perilaku Ibu Hamil dengan Status Gizi Ibu Hamil di Wilayah Kerja Puskesmas Padang Matinggi - Pane, Mustika Dewi; Hotmaida, Efni; Rambe, Muhammad Arsyad Elfiqah; Nasution, Nur Arfah (Universitas Aufa Royhan, 2023)
Behavior is a person's actions or actions in response to something and then becomes a habit because of the values believed. Nutritional status is the state of the body as a result of food consumption and the use of nutrients. This study aims to determine the relationship between the behavior of pregnant women and the nutritional status of pregnant women. This type of research is quantitative with a descriptive correlation design, with a cross-sectional study approach. The sample in this study were 80 pregnant women. With a sampling technique that is purposive sampling. The results of this study showed a p-value: 0.01 <0.05, so it was found that there was a Relationship between Behavior of Pregnant Women with the Nutritional Status of Pregnant Women at Public Health Center Working Area Padangmatinggi. Advice for pregnant women to increase the insight of pregnant women so that chronic energy deficiency does not occur and can improve good nutrition for pregnancy